Remodeling of the Immune Response With Aging: Immunosenescence and Its Potential Impact on COVID-19 Immune Response - Cunha, Lucas Leite; Perazzio, Sandro Felix; Azzi, Jamil; Cravedi, Paolo; Riella, Leonardo Vidal (Frontiers in Immunology, 2020)
Elderly individuals are the most susceptible to an aggressive form of coronavirus disease (COVID-19) mediated by SARS-CoV-2. The remodeling of immune response that is observed among the elderly could explain, at least in part, the age gradient in lethality of COVID-19. In this review, we will discuss the phenomenon of immunosenescence, which entails changes that occur in both innate and adaptive immunity with aging. Furthermore, we will discuss inflamm-aging, a low-grade inflammatory state triggered by continuous antigenic stimulation, which may ultimately increase all-cause mortality. In general, elderly are less capable to respond to neo-antigens, because of lower naïve T cells frequency. Furthermore, they have an expansion of memory T cells with a shrinkage of the T cell diversity repertoire. When infected by SARS-CoV-2, young people present a milder disease as they frequently clear the virus through an efficient adaptive immune response. Indeed, antibody-secreting cells and follicular helper T cells are thought to be effectively activated in young patients that present a favorable prognosis. In contrast, the elderly are more prone to uncontrolled activation of innate immune response that leads to cytokine release syndrome and tissue damage. The failure to trigger an effective adaptive immune response in combination with a higher pro-inflammatory tonus may explain why elderly do not appropriately control viral replication and the potential clinical consequences triggered by a cytokine storm, endothelial injury and disseminated organ injury. Enhancing the efficacy of the adaptive immune response may be an important issue both for infection resolution as well as for the appropriate generation of immunity upon vaccination, while inhibiting inflammaging will likely emerge as a potential complementary therapeutic approach in the management of patients with severe COVID-19.